Analysis of the Beautiful Concept in Marina Ads (Study of Semiotic Analysis on Marina UV White Hand & Body Lotion Advertisement) - Diana Amalia; Saifuddin Zuhri (Universitas Islam Balitar, 2022)
Advertising is information content that promotes a product or service to be known, demanded, and purchased by the public. However, without realizing it, advertisements are able to persuade and create a point of view for the audience. People are led to create a point of view based on what advertisers put on advertisements. The ability of advertising in creating a construction of reality or point of view and persuading individuals has brought about various changes in lifestyle and culture. Various products and services offered in television advertisements are in the form of primary needs and secondary needs. Examples of secondary needs that are currently considered very important for women are skincare or skin care from the body to the face. One advertisement for body care products is Marina UV White Hand & Body Lotion. This study aims to determine the meaning of the beautiful white concept in the Marina UV White Hand & Body Lotion advertisement. By using Roland Barthes' qualitative semiotic method (denotation, connotation and myth), it can be concluded that Marina's advertisement is able to break the myth that has been circulating in society regarding beauty and women. .